The genetic and observational nexus between diabetes and arthritis: a national health survey and mendelian randomization analysis - Peng Zhang; Wanbo Zhu; Yongkang Wang; Nikolaos Kourkoumelis; Chen Zhu; Xianzuo Zhang; Weiwei Zhang (Nutrition & Diabetes)
Abstract Background Diabetes mellitus (DM) and arthritis are prevalent conditions worldwide. The intricate relationship between these two conditions, especially in the context of various subtypes of arthritis, remains a topic of interest. Objective To investigate the relationship between diabetes and arthritis, with a focus on Rheumatoid Arthritis (RA), using data from the National Health and Nutrition Examination Survey (NHANES) and Mendelian Randomization (MR) analysis. Methods Data from six consecutive NHANES cycles from 2007 to 2018 were analyzed, involving 30,062 participants after applying exclusion criteria. The association between diabetes and arthritis was assessed using logistic regression. MR was employed to determine the causal relationship between the two conditions using Genome-Wide Association Study (GWAS) data. Results The prevalence of arthritis in diabetic patients was almost twice that of non-diabetic patients. Logistic regression showed a significant gross association between arthritis and diabetes with an OR of 2.90 (95% CI: 2.66–3.16). After adjusting for age, gender, race, and other factors, the association yielded an OR of 1.14 (95% CI: 1.00–1.29, p < 0.05). MR analyses indicated a significant association between Type 1 Diabetes and RA (OR = 1.407, p = 0.002), but no significant correlation was observed for Type 2 Diabetes. Conclusion There is an association between diabetes and arthritis, with potential genetic links between Type 1 Diabetes and RA.